RESULTS OF DETERMINATION OF BITUMEN MOVEMENT MODES AT DIFFERENT TEMPERATURES - Mallabayev, Odiljon; Khurmamatov, Abdugoffor; Yusupova, Nadira; Sarsenbayev, Nurlan (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article presents the results of determining the modes of bitumen movement at various temperatures, the results of reducing the viscosity of construction bitumen grade BNSHK-1 depending on the process temperature, and the results of determining the main parameters of the hydrodynamics of the mixing process (the angular velocity of the mixer is 31.4 rad/s).